Diagnostic Challenge of Gitelman Syndrome: A Rare but Significant Cause of Electrolyte Imbalance - Nessa, Lutfor; Singh, Arjan; Sharif, Muhammad Waqar; Enabi, Joud; Bashir, Mamoun (Journal of Clinical Nephrology, 2023)
Objective: This case study presents a young female patient diagnosed with symptomatic electrolyte disturbances, later confirmed as Gitelman syndrome (GS). It highlights the underlying pathophysiology and emphasizes the importance of its proper management. Background: GS is a rare genetic disorder affecting kidney electrolyte reabsorption, leading to symptoms like weakness, muscle cramps, fatigue, nausea, and vomiting. Diagnosis involves lab tests and genetic confirmation, with treatment comprising electrolyte supplementation and medications. Ongoing management is vital to prevent complications. Case presentation: A 23-year-old Caucasian female presented to the ED with sudden weakness in all extremities, thirst, and lightheadedness. Lab results showed hyperglycemia 166 (70-100 mg/dL), severe hypokalemia 1.1 (3.6-5.1 mmol/L), mild hypercalcemia 11 (8.9-10.4 mg/dL), and severe hypophosphatemia 0.6 (2.3-7.0 mg/dL). Incidentally, she had prior hypokalemia history from a motor accident hospitalization and managed it with KCl for a year but stopped when symptoms improved. She was treated with electrolyte replacement and discharged with oral potassium. Five days later, she returned with severe hypokalemia 1.3, mild hypercalcemia 10.7, and severe hypophosphatemia 0.6. A 24-hour urinary test showed distal convoluted tubulopathy indicative of GS. She was treated with replacement therapy and spironolactone, with instructions for ongoing supplementation and follow-up with a nephrologist. Discussion: GS is mostly caused by mutations in the SLC12A3 gene, affecting the kidneys’ sodium chloride cotransporter function, as confirmed in our patient. Conclusion: While GS has no cure, appropriate treatment with medication and dietary adjustments can enhance patients’ quality of life by maintaining electrolyte balance. Healthcare providers’ awareness is crucial for effective care and complication prevention.